Hidden truth : young men navigating lives in and out of juvenile prison - Reich, Adam D. (Adam Dalton), 1981- (University of California Press, 2010)
Hidden Truth takes the reader inside a Rhode Island juvenile prison to explore broader questions of how poor, disenfranchised young men come to terms with masculinity and identity. Adam D. Reich, who worked with inmates to produce a newspaper, writes vividly and memorably about the young men he came to know, and in the process extends theories of masculinity, crime, and social reproduction into a provocative new paradigm. Reich suggests that young men's participation in crime constitutes a game through which they achieve "outsider masculinity." Once in prison these same youths are forced to re.